1997
DOI: 10.1530/eje.0.1370172
|View full text |Cite
|
Sign up to set email alerts
|

One microgram is the lowest ACTH dose to cause a maximal cortisol response. There is no diurnal variation of cortisol response to submaximal ACTH stimulation

Abstract: There are many suggestions in the literature that the adrenal gland is more sensitive to ACTH in the evening than in the morning. However, all these studies in humans were conducted when the basal cortisol level was not suppressed, and were based on the observation that, after stimulation, the increases in cortisol differed, though the peak values were the same. To examine this, we established the lowest ACTH dose that caused a maximal cortisol stimulation even when the basal cortisol was suppressed, and used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 11 publications
(13 reference statements)
3
52
2
1
Order By: Relevance
“…In agreement with previous authors who defined the cut-off value for peak cortisol after 1 mg ACTH as 497-500 nmol/l (11,15,18,25), all our normal controls showed a peak greater than 500 nmol/l and this limit was considered as the 'pass' criterion for the test.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with previous authors who defined the cut-off value for peak cortisol after 1 mg ACTH as 497-500 nmol/l (11,15,18,25), all our normal controls showed a peak greater than 500 nmol/l and this limit was considered as the 'pass' criterion for the test.…”
Section: Discussionsupporting
confidence: 90%
“…In this context, sensitive tests for assessing adrenal reserve become of significant importance. In recent years, stimulation with low-dose ACTH has been used as a sensitive test to detect subtle changes in adrenal function, which would be missed if the standard ACTH test is used (10)(11)(12). The low-dose ACTH test, following dexamethasone suppression of endogenous ACTH, would therefore be a sensitive method to assess adrenocortical reserve in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Exact timing of blood sampling is, therefore, very important with this test, and dilution errors of the 250 mg corticotropin 1-24 ampoule can also occur. I assume that in the three patients in the paper of Ambrosi et al (10) in whom the IHT was normal but the response to 1 mg corticotropin was subnormal, blood sampling time or dilution of the ampoule was not quite exact, because a test that stimulates the adrenal maximally (19) theoretically cannot result in a smaller cortisol response than the IHT that stimulates plasma ACTH to between 100 and 300 pg/ml in normal subjects.…”
Section: Recommendations For Using Dynamic Testsmentioning
confidence: 97%
“…Dickstein et al (16) maintained that with the low-dose test, the cortisol response at 30 min after i.v. injection of corticotropin 1-24 is indistinguishable from that after 250 mg, since 1 mg was said to be 'the lowest ACTH dose to cause a maximal cortisol response' (19). Tordjman et al (18), however, found 1 mg stimulated cortisol less than 250 mg corticotropin 1-24.…”
Section: The Low-dose Corticotropin Testmentioning
confidence: 98%